Variability and change in the west Antarctic Peninsula marine system: Research priorities and opportunities - Henley, Sian F.; Schofield, Oscar M.; Hendry, Katharine R.; Schloss, Irene R.; Steinberg, Deborah K.; Moffat, Carlos; Peck, Lloyd S.; Costa, Daniel P.; Bakker, Dorothee C.E.; Hughes, Claire; Rozema, Patrick D.; Ducklow, Hugh W.; et al. (Progress in oceanography, 2019)
•The WAP shelf ecosystem is regionally important for krill and higher trophic levels.•Long-term climate change and short-term natural variability control sea ice dynamics.•Physical changes regulate ecosystem functioning, biogeochemistry and air-sea exchange.•The WAP is a model system for how sea ice changes can restructure polar ecosystems.•Future research requires international cooperation and interdisciplinary integration. The west Antarctic Peninsula (WAP) region has undergone significant changes in temperature and seasonal ice dynamics since the mid-twentieth century, with strong impacts on the regional ecosystem, ocean chemistry and hydrographic properties. Changes to these long-term trends of warming and sea ice decline have been observed in the 21st century, but their consequences for ocean physics, chemistry and the ecology of the high-productivity shelf ecosystem are yet to be fully established. The WAP shelf is important for regional krill stocks and higher trophic levels, whilst the degree of variability and change in the physical environment and documented biological and biogeochemical responses make this a model system for how climate and sea ice changes might restructure high-latitude ecosystems. Although this region is arguably the best-measured and best-understood shelf region around Antarctica, significant gaps remain in spatial and temporal data capable of resolving the atmosphere-ice-ocean-ecosystem feedbacks that control the dynamics and evolution of this complex polar system. Here we summarise the current state of knowledge regarding the key mechanisms and interactions regulating the physical, biogeochemical and biological processes at work, the ways in which the shelf environment is changing, and the ecosystem response to the changes underway. We outline the overarching cross-disciplinary priorities for future research, as well as the most important discipline-specific objectives. Underpinning these priorities and objectives is the need to better define the causes, magnitude and timescales of variability and change at all levels of the system. A combination of traditional and innovative approaches will be critical to addressing these priorities and developing a co-ordinated observing system for the WAP shelf, which is required to detect and elucidate change into the future.